OUTCOME OF THYROID STORM CASES IN 2023 AT HOSPITAL TELUK INTAN, MALAYSIA - Hassannuddin, Ahmad Affan; Sun, Choon Peng; Panerselvam, Nalini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Thyroid storm, also known as thyrotoxic crisis, is an acute, life-threatening condition induced by the excessive release of thyroid hormones in individuals with thyrotoxicosis that present with systemic involvement. Thyroid storm mortality is estimated to be 8 to 25% despite modern advancements in its treatment and supportive measures. It is now an uncommon condition because of earlier diagnosis and treatment of thyrotoxicosis. Thyroid storm is commonly associated with Graves' disease, but it may occur in patients with toxic nodular goitre or any other cause of thyrotoxicosis. Thyroid storm may be precipitated by a number of factors including intercurrent illness, especially infections. METHODOLOGY This is a retrospective audit which included all patients who were admitted for thyroid storm from January 2023 to December 2023. The data was collected from clinical notes and electronic medical records. RESULTS A total of 23 subjects were included in this audit, which predominantly were female at 87%. Median age of the study population is 40 with the youngest subject aged 13 and the oldest was aged 64. The mean Burch and Wartofsky score was 47. For identifiable causes of storm, 13 out 23 subjects (56%) were due to infection, mostly pneumonia, followed by 22% (5 subjects) due to undiagnosed hyperthyroidism and 17% (4 subjects) were due to defaulted treatment. There were two mortalities (8.7%). Both mortalities required intubation and presented with pulmonary oedema on arrival, and had Burch and Wartofsky scores of 50 and 60 respectively. Mortality rate for thyroid storm in 2023 was 8.7%. CONCLUSION Death from thyroid storm is not as common as in the past owing to its prompt recognition and aggressive treatment in an intensive care unit, but mortality is still approximately 10- 25%. Early detection and understanding of hyperthyroidism symptoms among the public are critically important. Analysing the outcomes of thyroid storms at Hospital Teluk Intan highlights the need for increased public education to prevent future deaths caused by thyroid storms.